Exercise Training in Children and Adolescents with Cystic Fibrosis: Theory into Practice - Craig A. Williams; Christian Benden; Daniel Stevens; Thomas Radtke (International Journal of Pediatrics)
Physical activity and exercise training play an important role in the clinical management of patients with cystic fibrosis (CF). Exercise training is more common and recognized as an essential part of rehabilitation programmes and overall CF care. Regular exercise training is associated with improved aerobic and anaerobic capacity, higher pulmonary function, and enhanced airway mucus clearance. Furthermore, patients with higher aerobic fitness have an improved survival. Aerobic and anaerobic training may have different effects, while the combination of both have been reported to be beneficial in CF. However, exercise training remains underutilised and not always incorporated into routine CF management. We provide an update on aerobic and anaerobic responses to exercise and general training recommendations in children and adolescents with CF. We propose that an active lifestyle and exercise training are an efficacious part of regular CF patient management.